The performance of agronomic traits, genetic variability, and correlation studies for yield and its components in some red rice (Oryza sativa) promising lines - Gusti Ray Sadimantara; Dewi Nurhayati Yusuf; Eka Febrianti; Sitti Leomo; Muhidin MUHIDIN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sadimantara GR, Yusuf DN, Febrianti E, Leomo S, Muhidin. 2021. The performance of agronomic traits, genetic variability, and correlation studies for yield and its components in some red rice (Oryza sativa) promising lines. Biodiversitas 22: 3994-4001. Improving a new variety commonly depends on the nature and magnitude of genetic variability and its utilization, followed by selection and evaluation before being released into new superior types. The present study aims to estimate the genetic variability and relation between yield and its related traits of the red rice promising lines. The experiment was arranged based on a randomized complete block design (RCBD) with three replications. Analysis of variance revealed significant differences among rice lines for 12 quantitative traits. The phenotypic coefficient of variation (PCV) value was higher than the genotypic coefficient of variation (GCV), indicating a negligible environmental influence in the phenotypic expression of traits. High heritability estimates coupled with high genetic advance were recorded for grain total per panicle and grain yield per hill. Grain yield observed a highly significant positive correlation with panicle length (0.63), percentage of filled grains (0.53), grain weight per panicle (0.54), and thousand-grain weight (0.52). It correlated negatively with days to 50% flowering (-0.61) and days to maturity (-0.48). The study indicated that panicle length, percentage of filled grains, grain weight per panicle, and thousand-grain weight are important yield-related traits and could be used for selection to improve the genetic potential of rice yield.